2017
DOI: 10.4103/1450-1147.203071
|View full text |Cite
|
Sign up to set email alerts
|

Can 18F-Fluoroestradiol positron emission tomography become a new imaging standard in the estrogen receptor-positive breast cancer patient: A prospective comparative study with 18F-Fluorodeoxyglucose positron emission tomography?

Abstract: Correct staging is the most crucial for the treatment outcome in cancer management. Molecular imaging with 18F-fluoroestradiol (FES) positron emission tomography-computed tomography (PET-CT) targets estrogen receptor (ER) and may have a higher incremental value in diagnosis by aiding specificity. We enrolled 12 female breast cancer patients prospectively and did 18F-FES PET-CT and 18F-fluorodeoxyglucose (FDG) PET-CT within 1 week interval time. Lesion detection sensitivity was compared for a total number of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 16 publications
4
43
0
4
Order By: Relevance
“…Five studies included lesion‐level results for nonbreast metastatic lesions. In the four smaller studies , all 26 ER‐positive lesions by IHC were also ER positive by 18 F‐FES PET, and all 6 ER‐negative lesions were ER negative by 18 F‐FES PET. (Sensitivity and specificity estimates below 100% are due to continuity corrections to stabilize calculations.)…”
Section: Resultsmentioning
confidence: 93%
“…Five studies included lesion‐level results for nonbreast metastatic lesions. In the four smaller studies , all 26 ER‐positive lesions by IHC were also ER positive by 18 F‐FES PET, and all 6 ER‐negative lesions were ER negative by 18 F‐FES PET. (Sensitivity and specificity estimates below 100% are due to continuity corrections to stabilize calculations.)…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, we defined this MLN lesion as false positive of 18 F‐FDG (2.9%). We will discuss these remaining 238 lesions in the following sections .…”
Section: Resultsmentioning
confidence: 99%
“…18 F‐FES was slightly higher in the sensitivity of lesion diagnosis (90.8% to 91.9%). In the study by Gupta et al, different results were observed in 10 treatment‐naive patients with ER‐positive breast cancer, where higher sensitivities in 18 F‐FDG PET compared with 18 F‐FES PET were reported (92.21% vs. 75.32%, respectively) . Notably, some lesions of ER‐positive characteristics were converted to ER‐negative phenotypes after treatment, and the heterogeneity of 18 F‐FES uptake was higher in patients with recurrent or metastatic breast cancer than untreated patients .…”
Section: Discussionmentioning
confidence: 95%
“…While 18 F-FES imaging has many benefits, it does have some limitations related to its ability to detect liver metastases because of the increased uptake of 18 From a sensitivity and specificity perspective, 18 F-FES has a high accuracy for the detection of ER+ lesions; which was illustrated in a meta-analysis conducted on 12 different studies that evaluated patients who had 18 F-FES imaging and compared FES results to biopsy/histopathology staining (Allred) results in patients with breast cancer (30-32, [37][38][39][40][41][42][43][44][45]. The meta-analysis demonstrated that for metastatic lesions, a test sensitivity of 100% and a specificity of 99% (30-32, [37][38][39][40][41][42][43][44][45]. When combined (primary lesion + metastatic lesions), FES imaging resulted in a sensitivity of 81% and a specificity of 80% when compared to biopsy/histopathology results (30-32, 37-45).…”
Section: Potential Benefits Of 18 F-fes Estrogen Receptor (Er) Imagingmentioning
confidence: 99%